(untitled) (Communications in Mathematical Research, 2021)
Multi-soliton configurations of a Moyal-type noncommutative deformed modified 2+1 chiral model have been constructed by dressing method several years ago. These configurations have no-scattering property. By making a second-order pole in the dressing ansatz, two-soliton configurations with genuine soliton-soliton interaction were constructed after that. We go on in this paper to construct a large family of multi-soliton configurations with scattering property by using the noncommutative extension of Bäcklund transformations defined by Dai and Terng in a recent paper.